A study on antioxidant depletion and degradation in polyolefin‐based geosynthetics: Sacrificial versus regenerative stabilization. Issue 2 (20th November 2015) - Müller, Werner W.; Jakob, Ines; Tatzky‐Gerth, Renate; Wöhlecke, Andreas
Abstract : Plastic products used in geotechnical engineering, so‐called geosynthetics, are often made of polyolefins (polyethylene or polypropylene) and stabilized against oxidative degradation by antioxidants (AO). Three types of AO "packages" are used: (P1) phenols and phosphites/sulfides, (P2) hindered amines (HAS) with a marginal stabilization P1 of the basic resin, and (P3) a combination of packages P1 and P2 with comparable amounts of phenol and HAS. We report about long‐lasting oven aging and water immersion tests at 80°C of 29 different polyolefin‐based products (geomembranes, geonets, and geotextiles). Pronounced differences in the degradation behavior were found depending solely on the type of AO package. In case of P1, the oxidative degradation is prevented by the AO. Autocatalytic oxidation only begins after depletion of AO and may lead to catastrophic failure depending on the environmental conditions. In case of P2, degradation starts right from the beginning. However, it is decelerated and proceeds gradually. In case of P3, the degradation behavior seems to be a superposition of the characteristics obtained for P1 and P2. Plotting the fractional loss of the AO in P1 and P2 as function of the square root of aging time, we identified two regimes of AO depletion. We suggest attributing this observation to the different mechanisms of AO depletion. POLYM. ENG. SCI., 56:129–142, 2016. © 2015 Society of Plastics Engineers